Degas's Breath and The Materiality of Pastel Veils. (2nd October 2021) - Kessler, Marni Reva
ABSTRACT: I consider materiality as a lens of art historical analysis and demonstrate how this critical framework drives us to examine the agency not just of the visible and tangible substance of a work, but also of the unseen experiences of the artist, the medium, and the viewer. Focusing on a pastel by Edgar Degas, I further contend that study of the material depths and visceral procedures of objects in this medium reveals that the artist, who would have blown away the excess dusts that accumulated as he worked, is uniquely embedded in the very material fabric of the image.